Stress influence on eating habits of first year Medicine students at a public university (Research, Society and Development, 2021)
Objective: Analyzing the stress influence on eating habits of university students. Methods: This work purposes a transversal study performed in a public university, involving first-year medicine academics, in the period from November 2020 to July 2021, defining a sample of 62 participants. Data collection was performed through an online questionnaire, produced in the Google Forms tool, containing 33 questions. The investigated variables were: associative variables (sociodemographic evaluation and food consumption) and outcome (stress). Descriptive and inferential analyses were executed from data obtained using statistical tests to establish relations between the variables. Results: The analyzes showed the majority were under 24 years old, resided without a partner, had a family income greater than three basic salaries, and presented BMI < 25. Moreover, the majority consumed fruits or fruit juices glasses, greenery, vegetables, leguminous, animal protein, fried and embed foods, goodies, excessive or insufficient amounts of carbohydrates, as well as consumed beef or chicken meat with fat or did not consume meat, used vegetable oil, did not add more salt in meal and was not used to exchange the lunch or dinner for snacks. It was observed that 32 participants considered themselves stressed. In inferential analysis, from the chi-squared test, the statistical significance occurred only for the stress variable and the fried, embed and goodies consumption. Conclusions: Stress has a significant influence on university students eating habits, which start to consume foods rich in carbohydrates and sodium, as fried, embed and goodies.